Effects of Exercise, Physical Activity and Sports on Physical Fitness and Body Composition in Children and Adolescents with Down Syndrome: A Systematic Review - Farias-Valenzuela, C; De Moraes-Ferrari, G (Springer Nature, 2025)
The objective of this systematic review (PROSPERO: CRD42024503648) is to analyze and describe the effects of physical activity, exercise and sport interventions on fitness in children and adolescents with DS, to promote the improvement of physical fitness or in body composition. Following the PRISMA guidelines, a search strategy was carried out in four databases (Pubmed, WoS, Scopus and SciELO). Inclusion criteria: studies that used exercise, physical activity or sports as an intervention, which sought to improve physical fitness in children or adolescents with DS. PEDro scale and RoB-2 were used to evaluate the quality of the articles. Of the total number of participants, there were 342 participants in the experimental group and 279 in the control group. To synthesize the information from the studies, it was ordered based on authors and year of publication; country; study design; population; age of participants; intervention; instruments for data collection; results.16 investigations met the selection criteria. 8 studies mention an improvement in muscle fitness, 3 on cardiorespiratory fitness, 2 on body composition, 5 on balance, one on agility and one on functional capacity. The limitations of the study include the heterogeneity of the interventions, which makes their comparison and recommendation difficult, and the small number of articles of high methodological quality according to the scales used. It is concluded that physical activity, exercise or sports interventions with a duration of 30 min to 75 min with a frequency of two or three times a week, for a period of 6 weeks up to 36 weeks and even for at least 5 consecutive days, produce improvements in the components of fitness in children and adolescents with Down syndrome. Therefore, it is a viable strategy to seek improvements in the physical condition of children and adolescents with Down syndrome, which could lead to a general improvement in the life of this population. This review received no external funding. © The Author(s) 2025.